Physiological and Biochemical Responses of Tomato Plants Grafted onto Solanum pennellii and Solanum peruvianum under Water-Deficit Conditions - Flávia Maria Alves (MDPI AG, 2021)
Grafting using suitable rootstocks mitigates the adverse effects caused by environmental stresses such as water deficit in the tomato crop. Solanum pennellii and Solanum peruvianum, the wild relatives of tomato, are used as rootstocks due to their tolerance to water deficit and soil-borne diseases. This study focused on evaluating physiological and biochemical responses of tomato plants grafted onto S. pennellii and S. peruvianum rootstocks during water deficit. The commercial tomato cultivar ‘HM 1823’ (HM) either self-grafted (HM/HM) or grafted onto S. pennellii (HM/PN), S. peruvianum (HM/PR), and ‘Multifort’ (HM/MU) rootstocks were subjected to water-deficit stress by withholding irrigation for eight days. The performance of the grafted plants under water deficit was evaluated using physiological and biochemical parameters in vegetative tissues of the grafted plants. Plants grafted using S. pennellii (PN) and S. peruvianum (PR) rootstocks showed higher values of water potential (Ψw), relative water content (RWC), net photosynthetic rate (A), and leaf water use efficiencies (WUE) compared to HM, HM/HM, and HM/MU. Plants grafted onto tomato wild relatives showed the lowest malondialdehyde (MDA) and proline content. This study demonstrated that the rootstocks of wild tomato relatives reduced the effect of water deficit to a greater extent through better physiological, metabolic, and biochemical adjustments than self-grafting plants.